Draft Genome of Australian Environmental Strain WM 09.24 of the Opportunistic Human Pathogen Scedosporium aurantiacum - Pérez-Bercoff, Åsa (Genome Announc, 2015)
We report here the first genome assembly and annotation of the human-pathogenic fungus Scedosporium aurantiacum, with a predicted 10,525 genes, and 11,661 transcripts. The strain WM 09.24 was isolated from the environment at Circular Quay, Sydney, New South Wales, Australia.